PEMBERIAN TERAPI MUROTAL QUR’AN TERHADAP NYERI SAAT PERAWATAN LUKA POST OP LAPAROTOMI DI RUANG KUTILANG RS.Dr.H.ABDUL MOELOEK PROVINSI LAMPUNG - Marliyana Marliyana (LPPM Sikes Panca Bhakti Bandar Lampung, 2018)
Pain is a subjektive and emotionally unpleasant sensation that is acquired related to actual or potential tissue damage, or describes the condition of the occurrence of damage. Patients who experience pain, they need to take action to reduce pain one of them is murotal Qur'an therapy. Based on data from RS.Hi.Abdul Moeloek in January to may 2017, that showed there are 250 patients or 24,6% who need other sugical procedures. The purpose of this study was to determine the effect that we give murotal qur’an therapy on reducing pain scale when wound care in the kutilang RS.Dr.Hi.Abdul Moelok Lampung Province. The type of this research is quantitative with a quasi-experimental design using the design of one group pre test and post test design. This research was conducted in june to august 2017. The subject in this study were 30 patients post laparotomy in kutilang RS.Dr.Hi.Abdul Moeloek Lampung Province. Hypothesis testing by paired sample t-test. Univariate analysis result obtained that before giving murotal qur’an therapy the average pain scale was 9,25 and after giving the murotal qur’an therapy on pain scale of post op laparotomy during wound care in the kutilang RS.Dr.Hi.Abdul Moeloek Lampung Province 2017 (p-value= 0,000).. For further research especially for nurse it is suggested to use murotal Qur’an, murotal Qur’an theraphy as an alternative in providing non-pharmacological therapy.